2018
DOI: 10.1039/c7ce01872j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and computational understanding of weak interactions in “bridge-flipped” isomeric tetrafluoro-bis-benzylideneanilines

Abstract: Structural and computational insights into inter-molecular interactions in isomeric bridge-flipped tetrafluoro-bis-benzylideneanilines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In principle, there are three basic stacking geometries between two aromatic rings: cofacial, parallel‐displaced and edge‐to‐face . Recently, investigation of the crystal packing involving fluorinated organic compounds confirmed that the molecular packing mode could be controlled or tuned via the formation of weak H ··· F, F ··· F and F ··· π contacts . It is well known that the trifluoromethyl group possesses a strong electron‐withdrawing character.…”
mentioning
confidence: 99%
“…In principle, there are three basic stacking geometries between two aromatic rings: cofacial, parallel‐displaced and edge‐to‐face . Recently, investigation of the crystal packing involving fluorinated organic compounds confirmed that the molecular packing mode could be controlled or tuned via the formation of weak H ··· F, F ··· F and F ··· π contacts . It is well known that the trifluoromethyl group possesses a strong electron‐withdrawing character.…”
mentioning
confidence: 99%
“…We have recently analysed the role of organic fluorine systematically in various series of molecules (Chopra, 2012;Chopra & Guru Row, 2011;Kaur et al, 2012Kaur et al, , 2016Kaur & Choudhury, 2014. In our recent studies, we have demonstrated the significance of fluorine-mediated interactions (C-HÁ Á ÁF, C-FÁ Á ÁF, and C-FÁ Á Á) in a series of fluorinated benzylideneanilines (Chopra, 2012;Chopra & Guru Row, 2011;Kaur et al, 2012Kaur et al, , 2016Kaur & Choudhury, 2014, azobenzenes (Karanam & Choudhury, 2013) and bis-benzylideneanilines (Dhingra et al, 2018). All the molecules studied earlier by us were nearly planar and conformationally less flexible.…”
Section: Introductionmentioning
confidence: 82%
“…At the same time, bridge-flipped isomeric pairs that are not isomorphous may serve as seeds for the preparation of new polymorphs of their formerly non-isomorphous counterparts, providing yet another means for obtaining new solid materials. Isomorphism among bridge-flipped isomers is rare, commonly being prevented by differences in structural features such as preferred molecular conformations and favored intermolecular interactions that include hydrogen bonding and Lewis acid–base contacts. On the other hand, several examples of isomorphous pairs are known. Our search for isomorphous bridge-flipped isomers has employed the premise that similar intermolecular interactions occurring in the two isomers would promote their isomorphism. This strategy has been pursued successfully by previous workers who used strong hydrogen-bonding interactions between carboxylic acids and amides to obtain isomorphous crystals in a chloro/methyl exchange .…”
Section: Introductionmentioning
confidence: 99%